To boundary or not: The structural bias of 'fair representation' in rural areas. (October 2020) - Martinus, Kirsten; Reilly, Benjamin
Abstract: Fair representation of different communities of interest is a central tenet of democracy. In Australia, governments at all levels historically employed rural weightings to maintain the representation of sparsely-populated regions. However, these have fallen out of favor as demands for one-person, one-vote equality have become the norm. This nominal equality can create other forms of bias in areas of uneven population which have distinct communities of interest, as is the case in many rural local governments. This paper explores this bias by unpacking findings of a ward boundary review in the rural local government Shire of Dandaragan in Western Australia. Drawing on interviews with councilors and community stakeholders, it examines different proposals for fair representation via ward and non-ward based structures. It finds that fair representation of all communities is challenged by inherent biases in the criteria for drawing ward boundaries that are often not well understood by those involved. It shows how a 'no ward' system which allows smaller communities to coordinate behind a single reputable candidate can generate fairer representation than a system of wards whose boundaries may or may not align with communities of interest. Highlights: Local governments in Australia can be based around a system of wards or elected 'at-large' in a no-ward district. Ward boundaries must by law be based around communities of interest and also reflect equality in councilor-to-elector ratios. These criteria are in tension in many rural areas. The findings of this paper highlight the perceived and actual bias which emerged in a ward boundary review of the Shire of Dandaragan, a rural local government area in Western Australia. Fair representation under various boundary options was challenged by inherent and structural biases often not well-understood by community stakeholders and decision-makers. We conclude that a no ward system can produce fairer representation than a system of wards which may not align with communities of interest given equality requirements when populations are unevenly distributed across wards.